The International Law Principle for People with Disabilities: Analyzing Access to Justice - Ridwan Arifin; Iqbal Baiquni; Januari Nasya Ayu Taduri; Rasdi Rasdi; Zikkri Zikkri (Unnes Law Journal, 2021)
Disability groups are one of the groups that are vulnerable to various violations of their rights. In fact, the protection of this group has been regulated both nationally and internationally. The International Convention on the Rights of Persons with Disabilities or the United Nations Convention on the Rights of Persons with Disabilities (CRPD) clearly outlines the principles that must be met in providing protection for persons with disabilities, ranging from: (1) respecting the inherent dignity, autonomy the individual including the freedom to make one's own choices, and the freedom of people; (2) non-discrimination, (3) full and effective participation and inclusion in society; (4) respecting the differences and acceptance of people with disabilities as part of human diversity and humanity; (5) equality of opportunity; (6) accessibility; (7) equality between men and women; and (8) respect for the evolving capacities of children with disabilities and respect for the right of children with disabilities to maintain their identity.